Effect of continuous renal replacement therapy on cardiac function in the maintenance hemodialysis patients with hypotension - LI Ping; LUAN Sen; XIAO Ying (Linchuang shenzangbing zazhi)
Objective Discuss the effect of continuous renal replacement therapy( CRRT)on cardiac function in maintenance hemodialysis patients with hypotension. Methods Through the difference in body weight,systolic pressure,diastolic pressure,NT-proBNP,LVD,LVID,LVPW,IVSD,LVEF,LVM and LVMI of 45 MHD patients with hypotension before and after CRRT treatment,who were not tolerated in ordinary hemodialysis,we analysised the correlation of the changes between blood pressure and NT-proBNP level,left ventricular ejection fraction,left ventricular mass loss,left ventricular mass index decreased. we valuated the role of CRRT in improving the cardiac function of MHD patients with hypotension. Results The NT-proBNP,LVD,LVID,LVPW,IVSD,LVM and LVMI were all lower in MHD patients with hypotension after CRRT,differences are statistically significant( P < 0.05). There was a positive correlation between the level of increased systolic pressure and the level of NT-proBNP decline,the level of left ventricular mass decline and the drop in the mass index of left ventricle after treatment( P < 0.05). There was a positive correlation between the diastolic blood pressure and the level of NT-proBNP decline after treatment( P <0.05). Conclusions The treatment of CRRT can improve cardiac function in MHD patients with hypotension effectively.